Students’ Achievements and Learning Strategies across Gender Differences - Kartika, Tyas Willy; Emaliana, Ive (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2016)
This case study is intended to investigate students’ achievement and learning strategies employed by high achievers in English learning process at a singlegender private Islamic high school in East Java, Indonesia, in which male and female students are put in separated groups. Instruments used in this study are document analysis and interview guidelines. It reveals that the stereotype which is told us female learners tend to outperform male learners in language learning is not applicable in this study. Another conclusion that can be inferred is that all high achievers from both schools employ all learning strategy types which are proposed by Oxford (1990) namely; direct strategies and indirect strategies.